Answer:
(x)^2 (y)^2
---------- + --------- = 1
4 3
Explanation:
The standard equation for an ellipse is
(x-h)^2 (y-k)^2
---------- + --------- = 1
a^2 b^2
The center is at (h,k)
The vertices are at (h±a, k)
The foci are at (h±c,k )
Where c is sqrt(a^2 - b^2)
It is centered at the origin so h,k are zero
(x)^2 (y)^2
---------- + --------- = 1
a^2 b^2
The center is at (0,0)
The vertices are at (0±a, 0)
The foci are at (0±c,0 )
The vertices are (±2,0) so a =2
The foci is 1
c = sqrt(a^2 - b^2)
1 = sqrt(2^2 - b^2)
Square each side
1 = 4-b^2
Subtract 4 from each side
1-4 = -b^2
-3 = -b^2
3= b^2
Take the square root
b=sqrt(3)
(x)^2 (y)^2
---------- + --------- = 1
4 3